Potential of Biofuels in the European Transition to Sustainable Energy - Aryan Ahmadi-Khoie (Scientific Papers Animal Science and Biotechnologies, 2023)
With the growing energetic uncertainty surrounding Europe and calls for a swift reduction of the European dependence on fossil fuels, it is important to look for sustainable alternatives that could replace these in an accelerated timeframe. For this task, biofuels have an essential advantage over most other renewable energy sources, in that it can make use of much of the existing energy infrastructure. For this reason, it could play an important role in the transition to a sustainable and energetically independent Europe. The main focus of this study is to review and compare the important biofuel synthesis processes which are applicable to the European region and to evaluate the possible extent, benefits and drawbacks of their expanded usage in the European Union. Results suggest that certain biofuels could have a big positive impact; however, while current production can still be successfully increased, scaling it to its potential can prove problematic until newer biofuel technologies mature.